2023
DOI: 10.1002/chem.202302415
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity and Magnetic Behavior in Benzenoids: Unraveling Ring Current Combinations

Luis Leyva‐Parra,
Ricardo Pino‐Rios,
Diego Inostroza
et al.

Abstract: Nowadays, an active research topic is the connection between Clar's rule, aromaticity, and magnetic properties of polycyclic benzenoid hydrocarbons. In the present work, we employ a meticulous magnetically induced current density analysis to define the net current flowing through any cyclic circuit, connecting it to aromaticity based on the ring current concept. Our investigation reveals that the analyzed polycyclic systems display a prominent global ring current, contrasting with subdued semi‐local and local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…On the other hand, in the case of 5-MR, the aromaticity in azulene is 1.5 times higher than in the free C 5 H 5 − ring. This increase and decrease in the aromaticity of the local rings with respect to their free forms could be explained by the formation of a homogeneous (global) ring current that couples to the local currents, as has been shown recently; 54 however, according to the results obtained, it is reasonable to say that the local current in 5-MR is higher than in 7-MR.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…On the other hand, in the case of 5-MR, the aromaticity in azulene is 1.5 times higher than in the free C 5 H 5 − ring. This increase and decrease in the aromaticity of the local rings with respect to their free forms could be explained by the formation of a homogeneous (global) ring current that couples to the local currents, as has been shown recently; 54 however, according to the results obtained, it is reasonable to say that the local current in 5-MR is higher than in 7-MR.…”
Section: Resultssupporting
confidence: 64%
“…The difference in the assignments of local aromaticity and free rings between the magnetic and delocalization criteria may be due to the fact that the quantification of aromaticity through the magnetic criterion is due to a response function to a perturbation (magnetic field) generating a global current that couples to the local currents thus causing an overestimation of the aromaticity in the local rings of the azulene. 54 In spite of this, the delocalization criterion results agree with the magnetic criterion and the Glidewell–Lloyd rule.…”
Section: Resultsmentioning
confidence: 63%
“…To clarify this possibility, we evaluated the magnetically induced current density using the GIMIC program at the TPSSh/aug-cc-pVQZ level. The ring current circuits, and their strengths were identified by analyzing current strength profiles, following a strategy previously reported in the literature. , Our analysis reveals that applying a magnetic field perpendicular to the molecular plane induces local ring currents around the hydrogens (see Figure a and Figure S1) with moderate strengths (≈4 nA/T) and that benzene exhibits a net ring current strength value of 12.1 nA/T at the same level. These local diatropic ring currents agree with the 3c–2e Li–H–Li σ-bonds revealed by AdNDP; however, it contrasts with the identified 6c–2e σ-bond, reported by Guha and co-workers.…”
Section: Resultsmentioning
confidence: 99%
“…Interpretations based on these local magnetic indices may be misleading and an extensive analysis combining current–density and magnetic shielding calculations is better suited for systems with polycyclic or heteroatomic rings. For planar (and nonplanar) polycyclic systems, the shielding cones from neighboring rings may overlap making interpretations based on magnetic shielding calculations challenging . For example, the multipath character in the current density of large acenes complicates the determination and quantification of local (and global) aromaticity. Calculations involving the π-electron component of the magnetic response suggested that helicenes are globally aromatic since they sustain a global diatropic (clockwise) ring current along their perimeter, ,, promoting the formation of a deshielding cone along the helical axis. The deshielding cone becomes more pronounced with increasing helicene size. , Thus, no local ring currents flow around any of the helicene’s 6-MRs, making it inappropriate to characterize one ring as more or less aromatic than another.…”
Section: Introductionmentioning
confidence: 99%